Hubungan Lama Menderita Dengan Kunjungan Rutin Pasien Hipertensi Di Puskesmas Pauh Kota Padang Tahun 2024 - Asyari, Dian Paramitha (Yayasan Jompa Research and Development, 2024)
Abstract Hypertension is the leading cause of death in the world WHO estimates that 22% of the world and 26.4% of people in Indonesia suffer from hypertension. Hypertension ranks as the disease with the highest number of visits in Padang city. Pauh Health Centre is the 3rd highest case of hypertension, but with the lowest visit of 1%. The purpose of this study was to determine the relationship between duration of suffering and routine visits of hypertensive patients at Puskesmas Pauh. This type of research is quantitative with a cross sectional design. The population in the study were hypertensive patients who visited the health centre, the sampling method used accidental sampling with a sample of 65 respondents. The research instrument used a questionnaire. Data were analysed univariately and bivariately using the Chi-Square test. The results showed 69.2% of respondents did not visit regularly, 56.9%, respondents suffered short-term (1-5 years). There is a relationship between length of suffering (p=0.047) with routine visits of hypertension patients at Puskesmas Pauh. Based on the results of the study, it can be concluded that there is a relationship between the length of suffering with routine visits of hypertensive patients. Keywords : Hypertention, Repeat visited, Primary Health Care, Padang.